Additional file 1 of Intelligent identification of medical and veterinary intracellular protozoa by using self-supervised learning - Veerayuth Kittichai; Morakot Kaewthamasorn; Naruchit Soiphet; Teerawat Tongloy; Santhad Chuwongin; Siridech Boonsang (Figshare, 2026)
Supplementary Material 1.
Keywords: Machine Learning in Bioinformatics; Digital Imaging for Blood Diseases; AI in cancer detection